Traserve: Tradesman Service Application - Azhan, Ashraff; Ab Aziz, Ruhaya (Applied Information Technology And Computer Science, 2025)
Traserve: Tradesman Service is a mobile app developed with Amirul Tech Service to streamline the booking of electrical and plumbing services in Johor Bahru. Replacing the current manual WhatsApp-based system, Traserve addresses challenges such as inefficient order handling, overbooking, and lack of payment and tracking systems. Built using the Flutter framework with Firebase backend, the app features secure user authentication, real-time messaging, and integrated payments. Developed using the Prototyping Model, the process includes requirement gathering, design, prototyping, user evaluation, refinement, and deployment. Traserve enhances service efficiency and customer satisfaction by offering a digital platform for booking, tracking, and managing maintenance services. It supports Amirul Tech Service's operations by improving order management, reducing scheduling conflicts, manage order history report and boosting operational growth.